Women's advances in agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
the sky must not fallWomen hold up half the sky, according to the Chinese proverb. Women also sustain more than half of ACP agriculture. In recent decades, much has been achieved in empowering women within the agricultural sector. However, recent...